Implementation Of Corporate Social Responsibility (CSR) Policies and Program Of Palm Oil Plantation Companies In PT Perkebunan Nusantara V Riau Province - Haq, Agung Nur Haq; Basuni, Sambas; Sunkar, Arzyana (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Riau Province is the province with the largest palm oil company in Indonesia, so that the implementation of CSR policies is mostly carried out by palm oil companies in Riau Province. This study aims to measure the performance of the implementation of CSR policies and programs of oil palm plantation companies. This research was carried out at a state-owned company (PTPN V) by taking four examples of garden units based on purposive sampling which were seen from the differences in the location of community life, 3 garden units were in Kampar Regency, and one garden unit in Rokan Hilir Regency. Data analysis was performed using the IPA method which compared the perceptions of the company and the community. The components of the questionnaire compilation for assessing perceptions consisted of the elaboration of statements taken from Government Regulation No. 47/2012 regarding the implementation of CSR and several literature books that explained the implementation of CSR well. The results of this study indicate that the performance of CSR policy implementation that has been implemented by PT Perkebunan Nusantara V is very good in terms of policy content and support, but it needs improvements in the aspects of transparency, CSR programs and results. Transparency and wider information disclosure are important points for affordability towards the target of providing better CSR for the future.